Revisiting T Cell Tolerance as a Checkpoint Target for Cancer Immunotherapy - Nüssing, Simone; Trapani, Joseph A.; Parish, Ian A. (Frontiers in Immunology, 2020)
Immunotherapy has revolutionized the treatment of cancer. Nevertheless, the majority of patients do not respond to therapy, meaning a deeper understanding of tumor immune evasion strategies is required to boost treatment efficacy. The vast majority of immunotherapy studies have focused on how treatment reinvigorates exhausted CD8+ T cells within the tumor. In contrast, how therapies influence regulatory processes within the draining lymph node is less well studied. In particular, relatively little has been done to examine how tumors may exploit peripheral CD8+ T cell tolerance, an under-studied immune checkpoint that under normal circumstances prevents detrimental autoimmune disease by blocking the initiation of T cell responses. Here we review the therapeutic potential of blocking peripheral CD8+ T cell tolerance for the treatment of cancer. We first comprehensively review what has been learnt about the regulation of CD8+ T cell peripheral tolerance from the non-tumor models in which peripheral tolerance was first defined. We next consider how the tolerant state differs from other states of negative regulation, such as T cell exhaustion and senescence. Finally, we describe how tumors hijack the peripheral tolerance immune checkpoint to prevent anti-tumor immune responses, and argue that disruption of peripheral tolerance may contribute to both the anti-cancer efficacy and autoimmune side-effects of immunotherapy. Overall, we propose that a deeper understanding of peripheral tolerance will ultimately enable the development of more targeted and refined cancer immunotherapy approaches.